GAMBARAN TINGKAT KELEMBABAN KULIT PADA PASIEN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA RSUD BULELENG - Putu Intan Daryaswanti (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2019)
Background: Etiology of pruritus uremic has not yet been found specifically, but there are risk factors of the pruritus such as dry skin, reduced pruritogenic transpidermal elimination, hyperparathyroid, high calcium, magnesium and phosphate levels. Pruritus is a common and sad symptom that affects patients with chronic kidney disease. Purpose: to describe the skin moisture level in patients with Chronic Kidney Failure who undergo Hemodialysis in the Hospital of Buleleng. Method: This research is a quantitative research using descriptive method design. The population of this study was CRF patients who underwent regular HD at Buleleng Hospital. Sampling using simple random sampling technique with a total of 52 respondents. Respondents studied were CRF patients who underwent regular HD twice a week with a description of characteristics including age, sex, education, occupation and length of HD. Result: showed that the majority of respondents (38.4%) were in the category of 30-45 years old with a greater number of male respondents (69.2%). Most of the respondents' education levels were in secondary education (42.3%) and respondents did not work as many as 10 respondents (19.2%). Furthermore, the length of HD is mostly for 0-5 years, which is as much as 75%. the skin moisture level of CRF patients undergoing Hemodialysis in Buleleng General Hospital found that all respondents obtained dry skin (100%). Patients who undergo HD for approximately 5 years have experienced dry skin. Conclusion: Chronic kidney failure can cause changes in the sweat glands and oil glands which cause the skin to lose its natural ability to moisturize itself. This condition can also be caused by metabolic changes in CRF, which are interrelated with the fluid volume of patients undergoing dialysis.